The improvement of the instrumental means for processing and analyzing of space information - S. A. Zolotoy; I. B. Strashko; D. S. Kotau; I. M. Nestsiarovich; V. V. Rouba; K. I. Kostyuk (Informatika)
The need of the creation of information system with specialized services which allow scientists and specialists to perform thematic processing of Earth remote sensing data, changing the data processing parameters in a certain way, and independently analyze the information received is shown.To achieve the goal of rapid provision of information, the development of specialized information system is considered on the example of the creation of the software package for the dissemination of operational space information, as well as a software package for predicting the yield of grain crops.The structure of the software package for the dissemination of operational space information is shown. The technical and functional characteristics of the separate components of the package are given. The relations of the subsystems of the package are shown during data receiving, processing, analyzing and providing information to interested specialists and researchers. Attention is drawn to the possibilities of wide application of the software package for the dissemination of operational space information for solving scientific and applied problems in various fields of knowledge.The practical application of vegetation indexes in the analysis of operational space information is shown. The data of the practical results of forecasting of the grain crops development, as well as the quantitative indicators of satellites sessions are presented. The possibility of further improvement and development of the created information system is shown.